The Role of Attraction, Accessibility, Amenities, and Ancillary on Visitor Satisfaction and Visitor Attitudinal Loyalty of Gili Ketapang Beach - Taufiq Ismail; Fatchur Rohman (Universitas Airlangga, 2019)
The 4A tourism components, including attraction, accessibility, amenities, and ancillary, become prominent variables to be explored for their impact on visitor satisfaction and attitudinal loyalty mainly for relatively new tourism destination. This research conducted at Gili Ketapang Beach located at Probolinggo Regency as this new destination got more attention among tourists in Indonesia. Direct survey and online survey were done to collect the data from the destination spot, which gained 41 useable questionnaires. Due to sample size constraint, this research uses Partial Least Square to analyze the relationship among variables. The finding confirms that only attraction and ancillary that significantly influences visitor satisfaction; while accessibility and amenities do not have a significant role in visitor satisfaction. Next, attitudinal loyalty influenced by attraction, ancillary, and facilities but not availability. Satisfaction indeed affects visitor attitudinal loyalty of Gili Ketapang Beach. Further, the mediation role of satisfaction is well proven to amplify the role of 4A tourism components, except for accessibility.